2005
DOI: 10.1177/1069397104273628
|View full text |Cite
|
Sign up to set email alerts
|

Confidence Judgments on Color Category Best Exemplars

Abstract: Although basic color terms and basic color appearances have been

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…However, in any Caucasus culture where we could compare information from at least three age groups, the content set of color terms in general -with minor exceptionsrepeated the list provided by the eldest group. (A similar conclusion was arrived at by Alvarado & Jameson 2005). Probably, this is evidence for the trend, where the language inter-generation transmission still helps to preserve notions, which already do not reflect the reality immediately.…”
Section: Resultssupporting
confidence: 72%
“…However, in any Caucasus culture where we could compare information from at least three age groups, the content set of color terms in general -with minor exceptionsrepeated the list provided by the eldest group. (A similar conclusion was arrived at by Alvarado & Jameson 2005). Probably, this is evidence for the trend, where the language inter-generation transmission still helps to preserve notions, which already do not reflect the reality immediately.…”
Section: Resultssupporting
confidence: 72%
“…9 And the discussion surrounding the empirical differences in the use of color semantics in bilingual Vietnamese-English individuals in Jameson and Alvarado (2003a, b) and Alvarado and Jameson (2005). and do not examine the kinds of code-switching circumstances just described.…”
Section: Article In Pressmentioning
confidence: 97%
“…While B&O and S&W are in favor of this thesis, other researchers raised some concerns. In Alvarado and Jameson (2005), it is observed that fast response times tend to accompany higher confidence and accuracy; however, longer response times are ambiguous with respect to accuracy and confidence.…”
Section: Rationalementioning
confidence: 99%